Arbitrage and the Forward Gold Premium - Hodgson, John S. (Quarterly Journal of Economics, 1974)
In a recent article in this Journal, John H. Makin 1 observed a positive relationship between the dollar forward premium on gold and the ratio of gold to dollar assets in international reserve portfolios. This, he concludes, shows that gold is not a sterile asset; it has an expected rate of return that acts as a yield variable in the calculus of central banks making portfolio choices between gold and dollar assets. expected rate of return on gold is represented by the size of the forward premium on gold, which mirrors expectations of capital gains to be realized in the event of appreciation (or revaluation) of gold with respect to the dollar. analysis, as Makin recognizes, depends crucially on the assumption that an observed forward premium on gold reflects expectations of an increase in the dollar price of gold. behavior of the forward gold premium, however, should reflect, in addition to expectations about the future price of gold, movements in the rate of return on dollar securities. Covered interest arbitrage between the dollar and gold should establish a positive relationship between the rate of interest on dollar securities and the forward gold premium, just as it creates a link between interest differentials and forward premiums in currency markets. If the three months' rate of return on dollar-denominated securities rises above the three months' (percentage) forward premium on gold by an amount greater than the costs of moving into and holding dollar securities, arbitragers can profit by replacing gold with dollar securities in their portfolios and simultaneously buying an equivalent amount of gold forward. On the other hand, if the rate of return on dollar securities falls below the (percentage) forward premium on gold by an amount greater than the costs of moving into and holding gold, arbitragers can profit by replacing dollar-security holdings with gold and selling an equivalent amount of gold forward.2 This demand and supply of forward gold by * I am indebted to Thomas D. Willett and Terry Rush for helpful comments, and to John H. Makin for making available his series on forward gold premiums. Suggestions by referees were also highly useful. 1. John H. Makin, Swaps and Roosa Bonds as an Index of the Cost of Cooperation in the 'Crisis Zone', this Journal, LXXXV (May 1971), 34956. Also see John H. Makin, The Composition of International Reserve Holdings: A Problem of Choice Involving Risk, American Economic Review, LXI (Dec. 1971), 818-32. 2. Arbitragers will be willing to extend their positions until the cost of moving into and holding the asset acquired rise so as to become equal to the